Onion Cultivars Released by La Consulta Experiment Station, INTA, Argentina - Galmarini, Claudio Romulo (American Society for Horticultural Science, 2020)
The onion crop is of great importance in Argentina and, with garlic (Allium sativum L.), is the main fresh vegetable exported. The principal market for Argentine onions is Brazil, with significant exports to Europe and the United States. About 450,000 t of onions are produced yearly on 22,000 ha, for the freshmarket and dehydration industries (Galmarini, 1998). Onion seed production is also important in Argentina; ≈50,000 kg of seed is produced annually by domestic and international seed companies.